Atmospheric and Climatic Drivers of Tide Gauge Sea Level Variability along the East and South Coast of South Africa - Bernardino J. Nhantumbo; Björn C. Backeberg; Jan Even Øie Nilsen; Chris J. C. Reason (Journal of Marine Science and Engineering, 2021)
Atmospheric forcing and climate modes of variability on various timescales are important drivers of sea level variability. However, the influence of such drivers on sea level variability along the South African east and south coast has not yet been adequately investigated. Here, we determine the timescales of sea level variability and their relationships with various drivers. Empirical Mode Decomposition (EMD) was applied to seven tide gauge records and potential forcing data for this purpose. The oscillatory modes identified by the EMD were summed to obtain physically more meaningful timescales—specifically, the sub-annual (less than 18 months) and interannual (greater than two years) scales. On the sub-annual scale, sea level responds to regional zonal and meridional winds associated with mesoscale and synoptic weather disturbances. Ekman dynamics resulting from variability in sea level pressure and alongshore winds are important for the coastal sea level on this timescale. On interannual timescales, there were connections with ENSO, the Indian Ocean Dipole (IOD) and the Southern Annular Mode (SAM), although the results are not consistent across all the tide gauge stations and are not particularly strong. In general, El Niño and positive IOD events are coincident with high coastal sea levels and vice versa, whereas there appears to be an inverse relationship between SAM phase and sea level.